Analysis of the Scope of Energy Subsidies and Suggestions for the G-20 Initiative - International Energy Agency (World Bank, Washington, DC, 2017)
When the G-20 leaders met on 24-25 September 2009 in Pittsburgh, USA, they agreed in their Communiqué that, building on the efforts of many countries to, reduce fossil fuel subsidies while preventing adverse impact on the poorest?, they were committed to, rationalize and phase out over the medium term inefficient fossil fuel subsidies that encourage wasteful consumption. This draft report has been developed jointly by the International Energy Agency (IEA), Organization of the Petroleum Exporting Countries (OPEC), Organization for Economic Cooperation and Development (OECD) and World Bank in response to this request. It draws on the relevant expertise and work of the four tasked organizations, but also on input and comments from other organizations and experts. The report includes: a) discussion of the scope of energy subsidies; b) estimates of energy subsidies, and identification of the gaps in the existing data and issues around the measurement of energy subsidies; c) modeling-based analysis of the implications of phasing-out energy subsidies on the economy, including socio-economic and trade impacts, the environment, and the energy sector; and d) suggestions for the implementation of phase-out of inefficient subsidies leading to wasteful consumption, drawing on country case studies, including discussion of how to address social impacts.